Molecular platform based on a spiroindolinonaphthopyran of the diphenyloxazole series for the creation of polychromogenic molecular systems. (November 2022) - Metelitsa, Anatoly V.; Chernyshev, Anatoly V.; Demidov, Oleg P.; Makarova, Nadezhda I.; Rostovtseva, Irina A.; Voloshin, Nikolai A.; Solov'eva, Ekaterina V.; Tupaeva, Inna O.; Mukhanov, Evgeny L.; Gaeva, Elena B.
Abstract: A spiroindolinonaphthopyran of the diphenyloxazole series along with photochromism possesses a number of chromogenic properties such as solvatochromism, ionochromism, solid state phasochromism and fluorescence. The nature of these effects is associated both with the possibility of the spiropyran existence under its two forms (cyclic and merocyanine) and with the peculiarities of the molecular structure, in particular, with the presence of a diphenyloxazole fragment. Photochromic properties of the spiroindolinonaphthopyran do not exhibit a drastic dependence on the nature of solvents, including those that are capable of specific intermolecular hydrogen bond interactions. In addition, good resistance to photodegradation in the mode of photochromic balance opens up possibilities for designing polychromogenic molecular systems based on them. The positive solvatochromism of the first type, which is noticeably manifested in the case of merocyanine isomers, allowed establishing the weak polarity of their ground state. Solvatochromism of the second type demonstrates a significant spectral contrast (up to 227 nm) due to the existence of an equilibrium of cyclic and merocyanine isomers. The intensity of the effect increases upon passing from toluene to DMSO due to the shift of the equilibrium towards the merocyanine isomers. The presence of a chelate center formed by the merocyanine oxygen atom and the nitrogen atom of the diphenyloxazole fragment allows observing ionochromic transformations of the spiropyran molecule associated with the formation of coloured complex compounds upon its interaction with Co, Cu, Ni, Zn, Cd, Mn ions. It has been established that solutions of Zn, Cd, and Mn complexes exhibit the negative photochromism properties. The change in the solid state of spirpyran is accompanied by a change in the ability to undergo photochromic transformations. Under standard conditions the spiropyran exhibits photochromic properties in the crystalline state, but not in the amorphous one. The combination of chromogenic properties makes it possible to implement fluorescent molecular switches, bipolar absorption switches, photodynamic chemosensors, and solid-state phase transitions control the chromogenic properties based on spiropyrans of diphenyloxazole series. The possibility of structural modification leading to an enhancement of some properties and/or a weakening of other ones makes it possible to consider a spiroindolinonaphthopyran of a diphenyloxazole series as a molecular platform for creating polychromogenic molecular systems with desired properties. Graphical abstract: Image 1 Highlights: Spiropyran of the diphenyloxazole series exhibits a combination of chromogenic properties. One molecule allows to implement several types of switches. Solid state phase transitions control the chromogenic properties. The studied spiropyran is a molecular platform for designing desired molecules.